A modelling of ionospheric delay over Chiang Mai province - Suwantragul S. (2014)
Satellite signals that propagate through the earth's ionosphere are delayed by the number of free electrons which vary depending on the local time of the day, seasons, solar cycle, geographical location of the receiver and the geomagnetic field. These effects of the delays can be reduced by a dual-frequency receiver, using L1 and L2 signals. However, the dual-frequency GPS receivers are expensive and not reliable when tracking satellites at low elevations. Single frequency receivers are more widely used because of their low cost and simplicity and can be corrected to remove the delay using the ionospheric model data contain in broadcast satellite message. Because the variation of free electrons is unpredictable, the model can improve the positioning accuracy by only 50 %. This paper presents some estimation of ionospheric delay over Chiang Mai region using the TEC data collected. Preliminary results will be presented and compared with the raw data.